2016
DOI: 10.1186/s12889-016-2874-7
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, treatment and control of type 2 diabetes among Chinese elderly and its changing trend for past decade

Abstract: BackgroundThis study aims to evaluate the awareness, treatment, control rate of type 2 diabetes and its risk factors among Chinese community elderly, and also examine the changing trend for the past decade.MethodsWe conducted two population-based cross-sectional studies in a representative urban area of Beijing in 2001 and 2010 respectively, using with the same method. A total of 2,277 participants (943 male, 1,334 female) in 2001 and 2,102 participants (848 male, 1,254 female) in 2010 were recruited. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 23 publications
3
40
0
Order By: Relevance
“…For example, diabetes has been established as an independent risk factor for CKD(11), and awareness rates for type 2 diabetes have been documented between 65–90%. (1214) A study performed among patients who were reportedly well-engaged with a healthcare provider system found greater than 70% of patients correctly identified that they had “high cholesterol” and greater than 90% correctly confirmed personal diagnoses of hypertension (HTN) respectively (12). Studies have found awareness of diabetes-related complications does vary, but remains higher than early stage CKD awareness (3–8%).…”
Section: Introductionmentioning
confidence: 99%
“…For example, diabetes has been established as an independent risk factor for CKD(11), and awareness rates for type 2 diabetes have been documented between 65–90%. (1214) A study performed among patients who were reportedly well-engaged with a healthcare provider system found greater than 70% of patients correctly identified that they had “high cholesterol” and greater than 90% correctly confirmed personal diagnoses of hypertension (HTN) respectively (12). Studies have found awareness of diabetes-related complications does vary, but remains higher than early stage CKD awareness (3–8%).…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 18 There are limited studies with respect to awareness, treatment and control rates of diabetes in Beijing and the existing studies were mostly conducted in certain population or district. 19 , 20 , 21 , 22 In 2005, the overall awareness, treatment and control rate in population from four districts of Beijing was 56.7%, 50.0% and 15.0%, respectively. 19 In order to prevent and control chronic diseases, the Chinese government has increased financial investment on health care and Beijing has implemented comprehensive measurements in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In elderly adults, pharmacologic management with multiple drugs leads to a low treatment adherence, given a higher number of side effects. Besides, non-pharmacologic treatments such as a diet and lifestyle interventions are generally less effective, since the modi cation of eating and physical activity habits is usually a di cult task 34,35 . Education has previously been described as a protective factor for cognitive impairment, as higher education allows the development of "cognitive reserve" and a lower educational level is associated with a 5.6 greater risk of dementia 36 .…”
Section: Discussionmentioning
confidence: 99%